G218(P) Normal oxygen saturation values; data from term infants using masimo radical 7. (12th March 2018) - Godden, C; Mullan, E; Mactier, HM; Hamilton, R
Abstract : Aims: Chronic lung disease affects up to a third of babies born prematurely in the UK. 1 For some, this necessitates discharge home on supplemental oxygen. Criteria for identifying these ex-preterms vary between units. Increasing use of formal saturation profiles using the newest saturation recording devices in apparently asymptomatic babies reveals previously unsuspected reduction in oxygen saturations. The significance of this is not clear as there are limited data on normative values in this population. A pilot study of oxygen saturation limits in 40 healthy term newborns was designed to define normative values, with the aim of better informing interpretation of oxygen saturation profiles in ex-preterms. Methods: Overnight saturation monitoring was undertaken in healthy term newborns aged 24–36 hours using the MASIMO Radical 7 device. Recording was for up to 12 hours and mothers logged pertinent events. Results: To date 19 studies have been completed. A 5000 replicate robust quantile bootstrap methodology with outlier detection 2 was used to give a 95% reference range with a 90% confidence interval for each respective value as below: (table 1) Significant dips to 74% occurred in 3 subjects, all coincident with handling, feeding and/or changing. Collecting data has been hampered by frequent movement artefact triggering alarms and resulting in removal of sensors. The study is ongoing, and a time-dependent reference range will be constructed using a hierarchical regression approach to summarising data, in order to deal with covariance and increase resolution of the final range. We anticipate that greater number of data points will result in widening of the reference range at the lower end. Conclusions: Interim data using the next generation of monitors demonstrate oxygen saturations>93% for>95% of the time, in healthy newborns, suggesting that this should remain the target for ex-preterm babies when discharged home. Recording normative data may be improved with a two point sensor application to minimise movement artefact. References: . RCPCH NNAP report 2017 on2016 data. . Horn Paul S, Amadeo J Pesce, Bradley E Copeland. A robust approach to reference interval estimation and evaluation . Clinical Chemistry1998;44(3):622–631.